EFFECTS OF VERMICAST TEA ON THE REMEDIATION OF SPENT ENGINE OIL CONTAMINATED SOIL - Okonkwo, Chinyere Jacinta; Dada, Ebenezer Olasunkanmi; Njoku, Kelechi Longinus (FUDMA JOURNAL OF SCIENCES, 2023)
The need to maintain the rising numbers of both serviceable and degenerating automobiles in Nigeria has led to the springing up of vehicle workshops in approved and unapproved locations, where mechanics discharge spent engine oil indiscriminately into the soil and water environments. It is therefore desirable to explore potentially affordable and sustainable remediation methods. This study examined the efficacy of vermicast tea for the remediation of spent engine oil contaminated soil. Spent engine oil contaminated soil was collected from an automobile workshop, and mixed with different concentrations (20%, 50%, and 100%) of vermicast tea. The total petroleum hydrocarbon (TPH), moisture content, organic matter content, pH, and cation exchange capacity (CEC) in the contaminated soils were determined on day one, day 21, and day 42, using standard procedures. It was found that the TPH concentrations reduced in both vermicast tea treated and untreated soils, but percentage reductions were higher in contaminated soils treated with vermicast tea (63.65% – 74.74%) than in soil without vermicast tea (59.85%). The moisture content, organic matter content, pH, and cation exchange capacity of the spent engine oil contaminated soil were impacted due to the presence of vermicast tea. Moreover, remediation was observed to be significantly higher (p<0.05) at day 42 of exposure to vermicast tea, than at day 21. These results imply that vermicast tea can hasten natural remediation of soil contaminated with spent engine oil. It is recommended that future studies on the use of vermicast tea to remediate spent engine oil-contaminated soil for a...